Evaluation of fluorescence‐guided surgery agents in a murine model of soft tissue fibrosarcoma. Issue 6 (28th December 2017) - Prince, Andrew C.; McGee, Andrew S.; Siegel, Herrick; Rosenthal, Eben L.; Behnke, Nicole K.; Warram, Jason M.
Abstract : Background and Objectives: Soft tissue sarcomas (STS) are mesenchymal malignancies. Treatment mainstay is surgical resection with negative margins ± adjuvant treatment. Fluorescence‐guided surgical (FGS) resection can delineate intraoperative margins; FGS has improved oncologic outcomes in other malignancies. This novel strategy may minimize resection‐associated morbidity while improving local tumor control. Methods: We evaluate the tumor‐targeting specificity and utility of fluorescence‐imaging agents to provide disease‐specific contrast. Mice with HT1080 fibrosarcoma tumors received one of five probes: cetuximab‐IRDye800CW (anti‐EGFR), DC101‐IRDye800CW (anti‐VEGFR‐2), IgG‐IRDye800CW, the cathepsin‐activated probe Prosense750EX, or the small molecule probe IntegriSense750. Tumors were imaged daily using open‐ and closed‐field fluorescence imaging systems. Tumor‐to‐background ratios (TBR) were evaluated. On peak TBR days, probe sensitivity was evaluated. Tumors were stained and imaged microscopically. Results: At peak, closed‐field imaging TBR of cetuximab‐IRDye800CW (16.8) was significantly greater ( P < 0.0001) than Integrisense750 (7.0), Prosense750EX (5.8), and DC101‐IRDye800CW (3.7). All agents successfully localized as little as 1.0 mg of tumor tissue in the post‐resection bed; cetuximab‐IRDye800CW generated the greatest contrast (2.5). Cetuximab‐IRDye800CW revealed strong tumor affinity microscopically; tumor fluorescence intensity was significantly greater ( P < 0.0004) than 0.2 mm away from tumor border. Conclusion: This study demonstrates cetuximab‐IRDye800CW superiority. FGS has the potential to improve post‐resection morbidity and mortality by improving disease detection.